Sphingosine-1-phosphate is a missing cofactor for the E3 ubiquitin ligase TRAF2 - Alvarez, Sergio Eduardo (2010)
Tumour-necrosis factor (TNF) receptor-associated factor 2 (TRAF2) is a key component in NF-κB signalling triggered by TNF-α1, 2. Genetic evidence indicates that TRAF2 is necessary for the polyubiquitination of receptor interacting protein 1 (RIP1)3 that then serves as a platform for recruitment and stimulation of IκB kinase, leading to activation of the transcription factor NF-κB. Although TRAF2 is a RING domain ubiquitin ligase, direct evidence that TRAF2 catalyses the ubiquitination of RIP1 is lacking. TRAF2 binds to sphingosine kinase 1 (SphK1)4, one of the isoenzymes that generates the pro-survival lipid mediator sphingosine-1-phosphate (S1P) inside cells. Here we show that SphK1 and the production of S1P is necessary for lysine-63-linked polyubiquitination of RIP1, phosphorylation of IκB kinase and IκBα, and IκBα degradation, leading to NF-κB activation. These responses were mediated by intracellular S1P independently of its cell surface G-protein-coupled receptors. S1P specifically binds to TRAF2 at the amino-terminal RING domain and stimulates its E3 ligase activity. S1P, but not dihydro-S1P, markedly increased recombinant TRAF2-catalysed lysine-63-linked, but not lysine-48-linked, polyubiquitination of RIP1 in vitro in the presence of the ubiquitin conjugating enzymes (E2) UbcH13 or UbcH5a. Our data show that TRAF2 is a novel intracellular target of S1P, and that S1P is the missing cofactor for TRAF2 E3 ubiquitin ligase activity, indicating a new paradigm for the regulation of lysine-63-linked polyubiquitination. These results also highlight the key role of SphK1 and its product S1P in TNF-α signalling and the canonical NF-κB activation pathway important in inflammatory, antiapoptotic and immune processes.